A Formative Evaluation of Rendezvous: a Platform for Knowledge Sharing and Entertainment - Chua, Alton Yeow Kuan (2016)
Web applications that offer entertainment rarely support knowledge sharing. Conversely, applications that are intended for knowledge sharing rarely offer entertainment. The intent of this paper is therefore to propose the coalescence of knowledge sharing and entertainment in a Web application. The objectives of this paper are twofold: (1) to introduce a prototype called Rendezvous, which serves as a platform for both knowledge sharing and entertainment and (2) to conduct a formative evaluation of Rendezvous by soliciting feedback and its appeal for users' intention to adopt. A two-stage data collection plan was used. First, qualitative feedback was obtained from a group of 38 participants through focus groups. Thereafter, a questionnaire was developed and administered to 124 participants to assess users' intention to adopt. On the whole, the behavioral intention to adopt Rendezvous seems promising. Factors that seemed to influence behavioral intention to adopt included perceived utility, perceived enjoyment, perceived ease of use and social influences.